Evaluation of Thyroid Cancer Risk After Laryngeal and Nasopharyngeal Radiotherapy - Ghaznavi, Hamid (Reports of Radiotherapy and Oncology, 2021)
Background: Nasopharyngeal carcinoma is an uncommon head and neck cancer, which is commonly seen in young people aged from 15 to 25 years. Laryngeal cancer, on the other hand, is the second most common cancer among head and neck cancers. The primary treatment for patients with these carcinomas is radiotherapy. Objectives: This study aimed at estimation of thyroid cancer risk, as an organ at risk after laryngeal and nasopharyngeal radiotherapy Methods: with permission from the author, data related to thyroid dose of 20 patients who underwent radiotherapy of laryngeal and nasopharynx cancer in Salmanian et al. paper were used, and using the BEIR VII model, we calculated thyroid cancer risk. Results: lifetime attributable risk (LAR) of thyroid increased up to 2.7% in the treatment of nasopharyngeal cancer and up to 1.8% in the treatment of laryngeal cancer. The highest LAR values belonged to the treatment of nasopharyngeal cancer. Conclusions: radiotherapy for nasopharyngeal and laryngeal cancers considerably increased the risk of thyroid cancer in patients undergoing radiotherapy; such that the risk increased by more than 2.5% at younger ages. It is recommended to use an advanced treatment technique to reduce thyroid cancer risk and perform follow-ups annually in terms of the status of the thyroid gland and its changes.